Optimasi Pemilihan dan Pengukuran Efisiensi Alat Berat Pada Pekerjaan Fondasi Bored Pile - Pramita Utami; Ida Farida (Institut Teknologi Garut, 2026)
This study aims to optimize the selection and measurement of heavy equipment efficiency in bored pile foundation work in the Intan Husada Hospital construction project. This study uses a quantitative method based on the analysis of productivity, work efficiency, and heavy equipment operating costs, referring to Permen PUPR No. 8 of 2016. The results showed that the productivity of heavy equipment drilling rig reached 8 m/h, excavator 0.025 m³/h, and dump truck 34.8 m³/h. The work efficiency of the drilling rig for 124 days reached 0.23%. In planning, 161 bored pile hole points were estimated at a cost of Rp. 607,591,552, but the realization in the field was only 138 points at a cost of Rp. 195,243,738. This study contributes to the field of construction management by providing empirical data related to the optimization of heavy equipment use to improve the efficiency of infrastructure projects, especially in soft soil conditions.